Sustainable utilization of wild fruits and respective tree byproducts as partial feed ingredients or supplements in livestock rations - Chisoro, Prince; Mazizi, Bulelani; Jaja, Ishmael Festus; Assan, Never; Nkukwana, Thobela (Frontiers in Animal Science, 2025)
The long-term survival of livestock production systems depends critically on the sustainable usage of resource-efficient strategies, such as the supplementation or replacement of conventional feed ingredients (CFI) like maize and soybean with less expensive, more effective, and locally accessible sources. Wild fruits and their byproducts (WFBP) from multipurpose trees (e.g. leaves, seeds) offer a promising low-cost non-traditional alternative dietary source of energy, protein, vitamins, minerals, oxycaretenoids, and bioactive substances that function at a cellular level in livestock. According to research these non-CFI can enhance livestock voluntary intake, digestibility, and overall performance while alleviating the heavy reliance on CFI. Conversely, the use of these alternative feed resources (AFR) necessitates a thorough evaluation of their nutrient composition, antinutritional factors (ANF), and proper inclusion levels. At low appropriate inclusion levels in livestock rations, the availability of optimal crude energy, crude protein content, and availability of necessary amino acids (AA) in these AFR, can be taken advantage of in saving costs and reducing demands for soybean and maize, which are the indisputable CFI for both livestock and man. This review synthesizes the current research status of WFBP looking at their nutritional profiles (energy, protein, minerals, fiber etc.) and their impacts in livestock productivity. Furthermore, this review will address potential processing techniques to lessen their drawbacks like ANF or palatability. By highlighting these issues, this paper seeks to provide a guide for the sustainable incorporation of these AFR into livestock diets, striking a balance between nutritional effectiveness and economic feasibility.